Human Resource Management across Generations within the Context of World of Work 4.0 - Renta Skýpalová; Hana Stojanová; Hermann Troger; Zdeněk Caha (Emerging Science Journal, 2023)
The aim of the paper is to evaluate the expectations of cohorts of workers from Generations X, Y, and Z with regards to their perceptions of what a "good workplace" is. Two research questions were formulated accordingly. Respondents representing workers from Generations X, Y, and Z, from Italy and Austria, were asked to consider and rate (on a 1-5 scale) eighteen criteria on work environment and managerial approach. Multi-sample testing was applied during processing with the ANOVA and Shapiro-Wilk and the Kruskal-Wallis test was subsequently used for multi-sample testing. The findings show that the most popular criterion for all three generational cohorts is "good work atmosphere", followed by "all employees are valued, treated, and rewarded fairly". Interestingly, generational differences were observed for "customer orientation", which was more important for Generation X, and "autonomous organization of work (time)", which was more important for Generations Y and Z. The most surprising result was the significance of corporate image, with less than 4% identifying this as an important issue across all three generations. These findings can help human resource managers create appropriate working environments and motivational tools that meet the real expectations of employees. Doi: 10.28991/ESJ-2023-07-03-013 Full Text: PDF